Development of technology for forming vacuum-arc TiN coatings using additional impulse action - Pinchuk, N. V.; Starikov, V. V.; Kniazieva, H. O.; Surovytskyi, S. V.; Konotopska, N. V. (Institute for Single Crystals, 2022)
The effect of supplying a constant and high-voltage pulse with duration of 10 μs on the formation of predominantly oriented crystallites and the stress-strain state of vacuum-arc TiN coatings at two pressures of a nitrogen atmosphere is analyzed. It is shown that the deposition of the coatings under conditions of high voltage cascading effect leads to the growth of crystallites with the texture axis [110]. and to a change in the stress-strain state (reduction of deformation in the group of crystallites with the axis [111]). The obtained results are explained by an increase in the mobility of atoms and ordering processes in the region of the displacement cascades formed under the action of bombarding high-energy ions accelerated in the field of high-wave pulse potential. Computer simulations of the main processes observed during deposition were performed.

Проаналізовано вплив подачі постійного та високовольтного імпульсу тривалістю 10 мкс на формування переважно орієнтованих кристалітів та напружено-деформований стан вакуумно-дугових покриттів TiN за двох тисків атмосфери азоту. Показано, що осадження покриттів в умовах каскадного впливу високої напруги призводить до зростання кристалітів з текстурною віссю [110] і до зміни напружено-деформованого стану (зменшення деформації в групі кристалітів з віссю [111] ). Отримані результати пояснюються збільшенням рухливості атомів і процесів упорядкування в області каскадів зміщень, що утворюються під дією бомбардуючих високоенергетичних іонів, прискорених у полі високохвильового імпульсного потенціалу. Проведено комп’ютерне моделювання основних процесів, що спостерігаються під час осадження.
Розробка методики формування вакуумно-дугових покриттів TiN при додатковому імпульсному впливі
Keywords: TiN; coating; pulse influence; computer simulation; duration; radiation factor; texture; deformation; імпульси; фізичні процеси; напружено-деформований стан; кристаліти; комп'ютерне моделювання; напруга